Design and Functional Testing of a QR Code–Based Attendance System Prototype in a Special Library for Improving Visitor Recording Efficiency - Nugraha, Davin; Aminudin; Agustine, Merryam (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
Purpose of the Research. Recording visitor attendance is an essential aspect of library management, as it supports service evaluation and institutional reporting. However, visitor recording in many libraries is still conducted manually, leading to inefficiency, data inconsistency, and potential recording errors. This study aims to design and test a QR Code–based attendance system prototype to improve the efficiency of visitor recording in a special library context, which has received limited attention in previous studies. Research Method. This study employs a system development research approach focusing on system design and functional testing. Data were collected through conceptual observation of visitor recording workflows, documentation studies related to system requirements, and functional testing of the developed prototype. This study is limited to prototype development and does not involve full operational implementation. Analysis Data. Analysis data was conducted using a descriptive-analytical approach by examining the results of system testing and relating them to Information System theory and Efficiency theory. Results. The results indicate that the proposed QR Code–based attendance system is capable of recording visitor data in a structured and computerized manner. The system demonstrates potential improvements in recording efficiency, particularly in terms of processing speed, ease of data management, and consistency of visitor data. Conclusions. This study concludes that the QR Code–based attendance system prototype has the potential to serve as an alternative solution for improving visitor recording efficiency in special libraries. This study contributes by providing a prototype-based approach and highlighting its potential efficiency in a special library context. Future research is recommended to implement the system in real operational settings and evaluate its long-term effectiveness Keywords: Information Science; Special Library; Attendance System; QR Code; Visitor Recording